2010
DOI: 10.1111/j.1365-2710.2009.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Teicoplanin-induced hypersensitivity syndrome with a preceding vancomycin-induced neutropenia: a case report and literature review

Abstract: Hypersensitivity syndrome associated with teicoplanin has rarely been reported. We report a case with a preceding episode of vancomyin-related neutropenia. A 47-year-old female with cervical spine infection was treated with vancomycin. Neutropenia occurred after 17 days of vancomycin therapy. Vancomycin was changed to teicoplanin, and the neutropenia resolved 4 days later. After 11 days of teicoplanin therapy, a new episode of hypersensitivity syndrome manifested as fever, bilateral neck lymphadenopathy, mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
1
14
0
4
Order By: Relevance
“…En effet, les effets secondaires imputables à la téicoplanine ne sont ni fréquents ni sévères : rash cutané (2 %), fièvre (1,5 %), bronchospasme (0,3 %), douleur au point d'injection (1,5 %), élévation transitoire des transaminases et/ou des phosphatases alcalines (2 %), élévation transitoires de la créatinine (0,5 %), troubles digestifs et neurosensoriels non spécifiques (1 %). Des effets secondaires hématologiques étaient parfois décrits à type d'hyperéosinophilie (3 %), thrombopénie (0,1 %), Tableau [9] à propos d'une femme âgée de 47 ans admise pour une spondylodiscite cervicale, traitée en première intention par la vancomycine puis relayée par la téicoplanine en raison de l'apparition d'une neutropénie. L'imputabilité dans les 5 cas a été classée comme probable.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…En effet, les effets secondaires imputables à la téicoplanine ne sont ni fréquents ni sévères : rash cutané (2 %), fièvre (1,5 %), bronchospasme (0,3 %), douleur au point d'injection (1,5 %), élévation transitoire des transaminases et/ou des phosphatases alcalines (2 %), élévation transitoires de la créatinine (0,5 %), troubles digestifs et neurosensoriels non spécifiques (1 %). Des effets secondaires hématologiques étaient parfois décrits à type d'hyperéosinophilie (3 %), thrombopénie (0,1 %), Tableau [9] à propos d'une femme âgée de 47 ans admise pour une spondylodiscite cervicale, traitée en première intention par la vancomycine puis relayée par la téicoplanine en raison de l'apparition d'une neutropénie. L'imputabilité dans les 5 cas a été classée comme probable.…”
Section: Discussionunclassified
“…Le HHV6 est le plus incriminé. Une corrélation a été établie entre la sévérité de la présentation clinique et le développement d'une réponse immune antivirale spécifique de HHV6 [9]. Pour notre patiente, on n'a pas pu mettre en évidence ce virus puisque la PCR n'était pas pratiquée.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Mild leukopenia was similarly observed in a cohort of 26 patients with endocarditis caused by Grampositive organisms, but in all cases it was reversible and did not require discontinuation of antibiotic therapy or administration of granulocyte-colony stimulating factor. Teicoplanin is considered a rare cause of drug-induced hypersensitivity syndrome (DHS), but Hsiao et al reported a case of hypersensitivity in a 47 year-old woman who developed vancomycin-associated neutropenia, and after switching to teicoplanin, developed DHS characterized by fever, bilateral neck lymphadenopathy, mild wheezing, hepatitis and increased CRP, followed by neutropenia and thrombocytopenia [97]. Previous cases of DHS reviewed by the authors were not associated with eosinophilia, neutropenia or thrombocytopenia.…”
Section: Neutropeniamentioning
confidence: 94%